Cerium and Its Oxidant-Based Nanomaterials for Antibacterial Applications: A State-of-the-Art Review - Qi, Manlin; Li, Wen; Zheng, Xufeng; Li, Xue; Sun, Yue; Wang, Yu; Li, Chunyan; Wang, Lin (Frontiers in Materials, 2020)
Infectious diseases caused by bacteria remain a serious and global problem in human health. Herein, the discovery and application of antibiotics, which has attracted much attention in the past years, has cured numerous infectious diseases and made huge contribution in biomedical field. However, the widespread use of the broad-spectrum antibiotics has led to the serious drug resistance for many human bacterial pathogens. Especially, the bacterial drug resistance decreases the therapeutic effect and leads to high mortality. Inspiringly, the introduction of nanomaterials in biomedical field makes it possible to overcome the difficulty in the bacterial drug resistance attributed to their unique antibacterial mechanism. Recently, a variety of metal- and metal oxide-based nanomaterials are fully integrated in antibacterial applications and achieve excellent performances. Among them, cerium and cerium oxide-based nanomaterials have received much attention worldwide. Remarkably, cerium oxide nanoparticles with lower toxicity act as effective antibacterial agents owing to their unique functional mechanism against pathogens through the reversible conversion of oxidation state between Ce(III) and Ce(IV). This article provides an overview of the state-of-the-art design and antibacterial applications of cerium and cerium oxide-based materials. The first part discusses the underlying antibacterial mechanisms for cerium and cerium oxide-based materials currently applied in biomedicine. The second part focuses on various antibacterial related materials and their applications. In addition, the existing problems and future perspectives of the cerium and cerium oxide-based materials make up the third part of this review. This paper could provide the possible mechanisms for antibacterial activities, various designs of cerium and cerium oxide-based materials and related antibacterial properties.